Chamber plans locomotive location here (Raton Range Raton, New Mexico, 1956)
Newspaper article on the Chambers plan to possibly move an old Santa Fe Locomotive to Ripley Park.
Master list item #: 13
File location is in the Raton file Cabinet
Keywords: McCulloch, Frank; Montoya, Joe; Howland, Hughie; Erwin, Wood; Ripley Park; La Mesa Park; Local History; Biography; Locomotive; Transportation; Race Track; Raton, New Mexico; Albuquerque, New Mexico; Colorado Springs, Colorado